Vertigo and Dizziness in Children: An Update - Virginia Fancello; Silvia Palma; Daniele Monzani; Stefano Pelucchi; Elisabetta Genovese; Andrea Ciorba (Children, 2021)
Background: Vertigo and dizziness are relatively infrequent in paediatric patients, but specific data on the prevalence of these disorders are limited and influenced by various factors, including the age of the examined population. These conditions often have a significant impact on patients’ and parents’ quality of life. The aim of this paper is to investigate the prevalence of different aetiologies of vertigo in the paediatric population through a systematic review. Methods: According to PRISMA guidelines, a systematic review of the literature was performed. Medline and Embase were searched from January 2011 through to 10 September 2021. The search yielded 1094 manuscripts, which were reduced to 7 upon the application of inclusion criteria. Results: A total of 2470 paediatric patients were evaluated by the selected papers. Vestibular Migraine was the most frequently diagnosed condition, occurring alone or in association with other diseases. Overall, audio-vestibular disorders represented the second cause of vertigo, and the prevalence appears to increase according to age growth. Over the years, even though we assisted in the amelioration of diagnostic rates, partially related to an improvement in diagnostic tools, the aetiology of vertigo remains still unclear in a variable percentage of patients. Conclusion: Vertigo in children, despite being an uncommon symptom, requires a multidisciplinary approach, often involving Paediatricians, Neurologists and Otorhinolaryngologists. A comprehensive evaluation of children suffering from vertigo is crucial for establishing a successful therapy and reducing parental worries.